'Elective' Ventilation. Issue 2 (1st January 2013) - Stammers, Trevor
Abstract The demand for organs prompted the first use of elective ventilation in the UK in the 1990s. Recently the shortfall in supply of organs has once again prompted calls for elective ventilation to be instituted even in patients who are not brain dead. This paper proposes that the term 'elective' ventilation is a misnomer and the term non-therapeutic ventilation (NTV) should be used instead. It is further argued that the practice of NTV in cases of severe stroke is unethical and has the potential of causing a variety of harms to the patient, their relatives, and the healthcare professionals working in transplant teams and this may result in a backlash of reductions in the number of organ donations.